Supporting the development of R & D and the innovation potential of post-socialist countries - Leal Filho, Walter (NATO science series. Science and technology policy, 2004)
The course was called to address problems created by a general lack of skills in research and development, a lack of local expertise on information and technology transfer, and a lack of experience in disseminating results from research and development in Caucasian and neighboring post-socialist countries. The topics include legal dimensions of inn.